2013
DOI: 10.1073/pnas.1311654110
|View full text |Cite
|
Sign up to set email alerts
|

Chemically armed mercenary ants protect fungus-farming societies

Abstract: Significance We document the behavioral interactions among three ant species: a fungus-growing host ant, a permanently associated parasitic guest ant, and a raiding agro-predator ant. We show that the presence of guest ants becomes advantageous when host ants are attacked by raider ants, because guest ants use alkaloid venom to defend their host ant colony. Furthermore, detection of the guest ant odors is sufficient to discourage raider scouts from recruiting nestmates to host colonies. Guest ants li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 31 publications
1
40
0
2
Order By: Relevance
“…This commitment to farming later led to the emergence of the "higher attines," including the Acromyrmex and Atta leafcutter ants that rear truly domesticated and coevolving cultivars on fresh plant-material substrates (22)(23)(24)(25). However, it has remained underappreciated that relatively unproductive farming in the lower attines has otherwise been very successful in coping with the nutritional challenges of an exclusive fungal diet, in maintaining homeostatic growth conditions for small gardens, and in controlling fungal pathogens and social parasites (26)(27)(28). The continued survival and diversification of these small-scale farming mutualisms over evolutionary time thus suggests that these ants have found ways to control potential conflicts emanating from the unavoidable sexual inclinations of their symbiotic cultivars.…”
mentioning
confidence: 99%
“…This commitment to farming later led to the emergence of the "higher attines," including the Acromyrmex and Atta leafcutter ants that rear truly domesticated and coevolving cultivars on fresh plant-material substrates (22)(23)(24)(25). However, it has remained underappreciated that relatively unproductive farming in the lower attines has otherwise been very successful in coping with the nutritional challenges of an exclusive fungal diet, in maintaining homeostatic growth conditions for small gardens, and in controlling fungal pathogens and social parasites (26)(27)(28). The continued survival and diversification of these small-scale farming mutualisms over evolutionary time thus suggests that these ants have found ways to control potential conflicts emanating from the unavoidable sexual inclinations of their symbiotic cultivars.…”
mentioning
confidence: 99%
“…One of these, Megalomyrmex symmetochus Wheeler, will defend host attine nests against attack by G. hartmani, act ing as "mercenaries" to drive off the invading predators. Adams et al (2013) also found that G. hartmani workers selectively avoid attacking attine nests occupied by M. sym metochus. The closest relatives of M. symmetochus (e.g., its sister species, Megalomyrmex wettereri Brandao; see Adams 2012) are all agro-predators like G. hartmani, indicating that that M. symmetochus apparently evolved from an agro-predator.…”
Section: Introductionmentioning
confidence: 77%
“…Echols (1964) reported finding G. hartmani on four occasions in Lucky, Louisiana while examining nests of the attine ant Trachymyrmex septentrionalis (McCook): "In all cases G. hartmani had killed most or all of the Trachymyrmex workers, and were occupying the entire nest." Other researchers have documented that G. hartmani is an "agro-predator" that attacks attine ants in the genera Trachymyrmex, Sericomyrmex, and Myrmicocrypta (Dijkstra and Boomsma, 2003;Adams et al, 2013;R. Adams pers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As estratégias de defesa podem ocorrer de forma passiva, onde operárias impedem a ação de intrusos bloqueando a entrada da colônia e câmaras internas com o próprio corpo (Wheeler & Hölldobler, 1985;Brandão et al, 2001;Fischer et al, 2015), ou construindo ninhos de difícil acesso com pequenas entradas crípticas (Belchior et al, 2012). A defesa ativa ocorre através do patrulhamento nos arredores do ninho (Yamamoto & Del-Claro, 2008), bombardeamento de químicos defensivos (Sorrells et al, 2011;Adams et al, 2013;Chen et al, 2013) e combate direto corpo a corpo contra os intrusos (Pacheco & Del-Claro, 2015; ver capítulo 4), com destaque para presença de castas de operárias morfologicamente modificadas para funções defensivas . No entanto, como em qualquer fenótipo, as estratégias de defesa de uma colônia de formigas não são perfeitas.…”
Section: Introductionunclassified